2014
DOI: 10.1002/2014jd021741
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced high-temperature ice nucleation ability of crystallized aerosol particles after preactivation at low temperature

Abstract: In cloud chamber experiments with crystallized aqueous ammonium sulfate, oxalic acid, and succinic acid solution droplets, we have studied a preactivation mechanism that markedly enhances the particles' heterogeneous ice nucleation ability. First cloud expansion experiments were performed at a high temperature (267-244 K) where the crystallized particles did not promote any heterogeneous ice nucleation. Ice nucleation at this temperature, however, could be triggered by temporarily cooling the crystallized part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 72 publications
2
29
2
Order By: Relevance
“…These are particles that have already acted as an IN, or have been scavenged by growing ice crystals or were simply exposed to a temperature lower than ∼ 235 K. Wagner et al (2014) investigated aerosol particles before and after pre-activation in the AIDA cloud chamber and showed that the IN efficiency of these particles increased as a result. Ice on the surface of the surrounding mountains and glaciers at JFJ will be sublime in conditions when saturation with respect to ice is < 1.…”
Section: Pre-activated Aerosolmentioning
confidence: 99%
“…These are particles that have already acted as an IN, or have been scavenged by growing ice crystals or were simply exposed to a temperature lower than ∼ 235 K. Wagner et al (2014) investigated aerosol particles before and after pre-activation in the AIDA cloud chamber and showed that the IN efficiency of these particles increased as a result. Ice on the surface of the surrounding mountains and glaciers at JFJ will be sublime in conditions when saturation with respect to ice is < 1.…”
Section: Pre-activated Aerosolmentioning
confidence: 99%
“…Thus, the phase state of the aerosol particles (represented by their bounciness) could play a role in the onset of activation, as hinted at in measurements by Ignatius et al (2016), Ladino et al (2014), andWagner et al (2014). As the cloud chamber is generally close to water saturation at the beginning of each expansion, an earlier activation to cloud particles would be expected than is seen here.…”
Section: Discussionmentioning
confidence: 53%
“…Ladino et al, 2014;Wagner et al, 2014). Thus, there could have been a higher chance of ice formation in the respective second cloud activation runs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of frozen solution pockets, ice crystal growth can start when the particle dissolves and the trapped ice is released. For crystalline particles, Wagner et al (2014) referred to this process as deliquescence-induced ice growth. When the pores have connections to the surface, ice crystal growth may be initiated by the pore ice as soon as the air becomes supersaturated with respect to ice.…”
Section: Theoretical Background Of Nucleation and Preservation Of Icementioning
confidence: 99%